2011
DOI: 10.1111/j.1365-2672.2011.05070.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of naringin derivatives against pathogenic strains

Abstract: Aims:  To study the antimicrobial activity of naringin (NAR), a flavonoid extracted from citrus industry waste, and NAR derivatives [naringenin (NGE), prunin and alkyl prunin esters] against pathogenic bacteria such as L. monocytogenes, E. coli O157:H7 and S. aureus. The relationship between the structure of the chemical compounds and their antagonistic effect was also analysed. Methods and Results:  The agar dilution technique and direct contact assaying were applied. NGE, prunin and NAR showed no antimicrobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(84 citation statements)
references
References 36 publications
2
79
1
2
Order By: Relevance
“…In fact, data demonstrate that an increase in chain length (10-12 carbon atoms) and modifying its structure increased the antibacterial activities. This shows that the structure of naringenin is important for interaction with the antibiotics in combination studies (Celiz et al, 2011;Lee et al, 2013). Synergy studies of natural products and antibiotics are increasing in order to assess their combination effects (Olajuyigbe and Afolayan, 2013).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…In fact, data demonstrate that an increase in chain length (10-12 carbon atoms) and modifying its structure increased the antibacterial activities. This shows that the structure of naringenin is important for interaction with the antibiotics in combination studies (Celiz et al, 2011;Lee et al, 2013). Synergy studies of natural products and antibiotics are increasing in order to assess their combination effects (Olajuyigbe and Afolayan, 2013).…”
Section: Resultsmentioning
confidence: 93%
“…It contains two benzene rings linked together with a heterocyclic pyrone ring (a class of cyclic compounds) (Tripoli et al, 2007). It is believed to possess antibacterial (Celiz et al, 2011), antioxidant, anticancer anti-inflammatory and immunomodulatory properties (Goldwasser et al, 2011;Khachatoorian et al, 2012;Lee et al, 2013). The purpose of this study was to evaluate the antibacterial activities of naringenin on its own, as well as assess the combinatory antibacterial effects of naringenin and antibiotics against methicillinsensitive and methicillin-resistant strains of S. aureus (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Naringin (NR) is a bioflavonoid found in grapefruits and other citrus species (Figure 1). It has been shown to exhibit various pharmacological and therapeutic properties, e.g., antimicrobial (Céliz et al, 2011), antimutagenic (Jagetia et al, 2007), anticancer (Li et al, 2013), anti-inflammatory, cholesterol-lowering, and antioxidant effects (Jeon et al, 2002). Few studies have reported the cardioprotective effect of NR against isoproterenol (ISO)-induced myocardium infarction (MI) in rats (Rajadurai & Prince, 2006;Rajadurai et al, 2007).…”
Section: +mentioning
confidence: 99%
“…Citrus flavonoids, in particular, are recognized as antioxidants (Procházková et al 2011;Yu et al 2014;Asikin et al 2015), antifungals (Buer et al 2010), antimicrobials (Vikram et al 2010;Cushnie and Lamb 2011;Céliz et al 2011), and even accelerating wound and disease healing (Neves et al Neves et al 2010;Arab and Liebeskind 2010;Codoñer-Franch and Valls-Bellés 2010;Wang et al 2014). In plants, flavonoids appear to play defensive roles against pathogens, including bacteria, fungi and viruses; these are generally found in glycosylated forms in plants, and the sugar moiety is an important factor determining their bioavailability (Agati et al 2012).…”
Section: Introductionmentioning
confidence: 99%